Verification Method for Determination of Melting Temperature and Enthalpy Changes (âˆ†H) Using Differential Scanning Calorimeter - Warmiati, Warmiati; Wijayanti, Wijayanti (Journal of The Indonesian Society of Integrated Chemistry, 2023)
Verification of measurement method for determination of melting temperature and enthalpy changes using Differential Scanning Calorimeter has been carried out. This study was done to ensure that the method used can be applied in the laboratory with valid results and uncertainty. The verification method in this research consists of accuracy and precision. Accuracy was done by comparing measurement results with reference values using the t-student test. Precision can be seen in its repeatability and reproducibility. In this study, method verification of melting temperature measurement was carried out by thermal analysis using Differential Scanning Calorimeter (DSC) based on ISO 11357-3: 2018 method concerning determining temperature and enthalpy changes in melting and crystallization. The results showed that the method used to determine melting temperature and enthalpy changes (âˆ†H) had met the repeatability and reproducibility requirements. The RSD (Relative Standard Deviation) value was less than 2%, and the accuracy met the acceptance requirements with a t-count smaller than the t-table in a 95% confidence level. It means that the results are not significantly different from reference values, so the method can be used in the laboratory. Keyword: verification method, melting temperature, differential scanning calorimetry